Predictors, Risk Factors and Clinical Features Associated with Severe Dengue Fever - Amir Rashid; Amer Fakhr; Abdul Rehman Azeem; Abdul Rehman Arshad; Waqas Ahmed; Yastoor Ahmed Baig (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study predictors, risk factors and clinical features associated with severe Dengue fever on basis of initial symptom onset, laboratory investigations and physical findings. Study Design: Cross-Sectional Analytical Study. Place and Duration of Study: Dengue Ward, Pak Emirates Military Hospital Rawalpindi, Pakistan from Dec 2021to Mar 2022. Methodology: Study included 198 hospitalized, serologically proven cases of dengue fever. Patient demographics, symptoms, laboratory parameters and disease complications including bleeding, pleural effusion, ascites were recorded. Parametric tests were done for normally distributed continuous variables. Comparison of means was done for categorical variables. Pearson coefficient was used for quantitative variables. A p value of